Islamophobia: Definition, History, and Aspects - Nihaya Jaber (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2022)
This literature review draws on the available evidence regarding Islamophobia in the West. Despite the revolutionary ideas in regard to human rights, Muslims are still being persecuted in different countries and mistreated daily. Islamophobia is a current dilemma for Muslims who are suffering from a lot of abuse as a result of misconceptions about Islam in the face of the refugee crisis, some events in the Middle East, terrorism under the pretext of Islam, and prejudicial representation of Muslims in Western media and politics. Consequently, Muslims in the West are frequently misconstrued and affected badly because of their religion. This paper starts by defining the word ‘Islamophobia’ and tracking its origin. Then it tries to look back in history for the main events leading to the eruption of this phenomenon. Lastly, it sheds light on four aspects of Islamophobia which are violence, prejudice, discrimination, and exclusion.